2005
DOI: 10.1080/00222930400016762
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of natural histories and karyotypes of two closely related ant‐eating spiders,Zodarion hamatumandZ. italicum(Araneae, Zodariidae)

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 10 publications
(16 reference statements)
0
19
0
1
Order By: Relevance
“…Such ant‐mimicry is known for few other species of this genus (e.g. Pekár, Král & Lubin 2005b; Pekár et al. 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Such ant‐mimicry is known for few other species of this genus (e.g. Pekár, Král & Lubin 2005b; Pekár et al. 2005).…”
Section: Discussionmentioning
confidence: 96%
“…The above‐mentioned mechanisms were all found in polyphagous spiders. Field surveys on the association of Zodarion spiders in the Eastern Mediterranean revealed that each species exhibited strong prey specificity and adaptations for certain ant species (Pekár, Král & Lubin 2005b; Pekár et al. 2005; Pekár & Toft 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They are restricted almost exclusively to the Palearctic region with at least 35 species reported for the Iberian Peninsula (Platnick 2012). Available data on their biology show that all species are compulsory ant eaters (Wiehle 1928; Cushing and Santangelo 2002; Pekár 2004; Pekár et al 2005a,b, 2011). Some Zodarion spiders (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the 130 species seem to have small distribution ranges, restricted to a few hundred square kilometres (Bosmans 1994;. Only a few species extended their range beyond the Mediterranean (Snazell and Bosmans 1998;Askins 1999;Ř ezáč 2002;Pekár et al 2005b).…”
Section: Zodarion Rubidummentioning
confidence: 98%